Nutrient content of diet affects the signaling activity of the insulin/target of rapamycin/p70 S6 kinase pathway in the African malaria mosquito Anopheles gambiae - Arsic, Dany; Guerin, Patrick (My University, 2008)
Regulation of female mosquito feeding and reproduction plays a central role in their disease-vector competence. In this study we show that Anopheles gambiae mosquitoes engorged on albumin, amino acid and saline meals the same way as on blood, whereas sucrose evoked a typical plant nectar feeding response. Among the artificial diets, only the albumin-containing ones allowed follicular development. The target of rapamycin (TOR)/p70 S6 kinase (S6K) pathway has been identified as an essential nutrient-sensing tool controlling egg development in mosquitoes under the control of regulating inputs from the insulin pathway. We assayed the early response of TOR, S6K, tuberous sclerosis (TSC2), insulin receptor (INR) and two insulin-like peptides (ILPs) by quantitative real-time PCR assessment of mRNA levels and immunoblotting of phosphorylated active TOR and S6K in An. gambiae ovary and brain 3 h after engorgement. We show that transcript levels of s6k and members of the insulin pathway are readily affected by nutrients (especially one ILP in the head) and that the TOR/S6K phosphorylation is able to react quickly to a meal to an extent which depends on the true nutritive value.
Keywords: Anopheles gambiae; Oogenesis; Target of rapamycin; p70 S6 kinase; Amino acid signaling